Stones in the Landscape: Memory and Postmemory in the Yiddish Poems of David Fram - Frankel, Hazel (2017)
Until the Holocaust in Lithuania annihilated 90% of its community between 1941 and 1944, Yiddish was a fully lived language with its own rich history and literature. David Fram escaped the genocide, having left his shtetl, the market town of Ponevezh in 1927. Once in South Africa, committed to the preservation of his mameloshn, his mother tongue, he created a rich body of Yiddish poetry. Though little known, his poems offer insights into the understanding of a particular Jewish survivor testimony as well as into the Lithuanian Holocaust more generally. Through detailed analysis of specific poems, this paper argues for their continued relevance, providing a valuable space for an account of aspects of memory and postmemory. In making them available to a wider audience through my own translations and transliterations in this small act of retrieval, my hope is to preserve a literary heritage and to memorialize a lost world.
Keywords: David Fram -- Yiddish -- poetry -- Holocaust -- memory -- postmemory